Menghindari Perangkap Judi Online Dan Perilaku Konsumtif Top Up Game Online Melalui Psikoedukasi Remaja Tangguh Dalam Kegiatan KKN Di Desa Kersamenak - Wasalma, Ahwa Rizki; Salsha Putri Aisyah N; Saputri, Rizka; Mutmainah, Mutiara; Firdaus, Muhammad Rifqi; Khoirunnisa, May Hanny; Wijaya, Hany Duta; Subhan, Daris; Umniyah, Alya; Putra, Akhmal Arya; Sandi (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2024)
This community service program aims to provide psychoeducation to teenagers in Kersamenak Village about the dangers of online gaming addiction and how to avoid the traps of online gambling often associated with it. The program was implemented using the Service Learning method through observation, socialization, and Focus Group Discussions (FGD). The primary socialization activity was held in the afternoon to ensure maximum participation without disrupting the teenagers' daily routines. Through FGD, participants were encouraged to openly discuss the effects of game addiction and strategies for self-control. The results of this program showed an increase in teenagers' awareness of the risks of online gaming addiction and a better understanding of time management and responsible technology use. Support from PKK members and local residents played a crucial role in the program's success. This initiative is expected to be further developed to reach more teenagers in other areas.